ABO and Rh blood group genotypes in a cohort of Saudi stem cell donors. (13th February 2018) - Alzahrani, M.; Jawdat, D.; Alaskar, A.; Cereb, N.; Hajeer, A. H.
Summary: The ABO and rhesus (Rh) blood group antigens are the most frequently studied genetic markers in a large group of people. Blood type frequencies vary in different racial/ethnic groups. Our objective was to investigate the distribution of the ABO and rhesus (Rh) blood groups by molecular typing method in a population of Saudi stem cell donors. Our data indicate that the most common blood group in our population is group O followed by group A then group B, and finally, the least common is group AB.